HIGH-SPEED DEVICE FOR ANALOG-DIGITAL CONVERSION OF SIGNALS WITH CORRECTION OF TIME INSTABILITY IN THE FREQUENCY DOMAIN - BORTNYK, GENNADIY; BORTNYK, SERHII; KYRYLYUK, SERHII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper proposes a method of expanding the dynamic range of a high-speed analog-to-digital signal conversion device based on the correction of the temporal instability of the output signal. It was established that the discretization of the input signal in parallel analog-to-digital converters (PADC) is accompanied by a deviation of the actual moments of formation of signal readings from their nominal position on the time axis. As a result, the phenomenon of temporal instability of the PADC output signal occurs. This leads to the appearance of parasitic frequency components in the frequency spectrum of the output signal of the converter, which narrow the dynamic range of the analog-to-digital conversion device.The adjustment process consists of two stages: evaluation and compensation. At the first stage, the value of temporal instability is evaluated. The temporal instability of the PADC output signal is a difficult dynamic parameter to control. This is due to extremely small numerical values of this parameter, which in modern integrated PADC is within picosecond units. To assess temporal instability, it is suggested to synchronize the frequency of the input test signal of a sinusoidal form with the frequency of the formation of output readings. Then, diluted output readings are used, corresponding to the transitions of the sinusoid through zero, that is, at the moments of maximum steepness of the input signal. In contrast to the general sampling rule, in this case, the period of the sinusoidal test signal must be a multiple of the sampling period. Time instability error compensation is performed in the frequency domain. The structure of a high-speed analog-to-digital conversion device based on the parallel expansion of several PADC channels is given. Analysis of the effectiveness of the proposed method confirmed that thanks to the developed method, it is possible to expand the dynamic range of a 14-bit high-speed device by 22-36 dB in the operating frequency band.
Keywords: analog-digital conversion device; parallel analog-digital converters; temporal instability; dynamic range